Dynamical behaviour of the autonomous - Costa, Ilidio (1999)
This paper describes an Autonomous Mobile Robot project, developed by three senior students from the Industrial Electronics Engineering course during their probation period. A large robot was built in order to participate on the Festival International de Science et Technology 1998 in Bourges, France. In this contest, besides other tasks, the robot was supposed to follow a track painted on the floor. A dynamical approach was used for that purpose and this paper refers to the trajectory control module responsible to keep the robot centered and properly oriented as it travels through the track.